(untitled) (Scientific journal of the Fergana State University, 2023)
The article analyzes the beginning of the popular uprising and protests in Turkestan as a result of the Russian empire’s participation in World War I and the colonial administration was forced to rely on the troops of the Turkestan Military District due to difficulties in suppressing the uprising.